Improving drilled cuttings lifting using polypropylene beads in water- based mud at different annular mud velocities - Wan Sulaiman, Wan Rosli (International Journal of Engineering and Technology, 2017)
An effective drilled cuttings lifting from the bottom hole to the surface improves drilling performance. The transportation of drilled cuttings becomes more challenging when drilling a high angle or horizontal well. A sufficiently high annular mud velocity is essential to prevent drilled cuttings from settling and forming stationary beds on the low side of a hole. This can cause several drilling problems such as high torque and drag, stuck pipe, etc. This problem has been addressed via an experimental work which studied the effect of annular mud velocities on drilled cuttings removal using water-based mud with polypropylene beads in vertical, deviated, and horizontal holes. It was accomplished using a 3.96 m long flow loop which comprised 50.8 mm transparent acrylic section with a simulated drill string. The annular mud velocity was varied from 0.27 in/s to 1.06 m/s at ambient condition. The experimental results showed that increase in annular mud velocity has improved hole cleaning, i.e., cuttings transport ratio experienced an improved performance in the turbulent flow than in laminar flow. The findings further demonstrated that the presence of polypropylene beads in water-based mud has contributed positively to the performance of drilled cuttings lifting in a vertical hole by 9% in a turbulent flow.